2018
DOI: 10.1038/s41467-017-02406-2
|View full text |Cite
|
Sign up to set email alerts
|

Circulating exosomes suppress the induction of regulatory T cells via let-7i in multiple sclerosis

Abstract: Multiple sclerosis (MS) is a T cell-mediated autoimmune disease of the central nervous system. Foxp3+ regulatory T (Treg) cells are reduced in frequency and dysfunctional in patients with MS, but the underlying mechanisms of this deficiency are unclear. Here, we show that induction of human IFN-γ−IL-17A−Foxp3+CD4+ T cells is inhibited in the presence of circulating exosomes from patients with MS. The exosomal miRNA profile of patients with MS differs from that of healthy controls, and let-7i, which is markedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
136
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(139 citation statements)
references
References 59 publications
3
136
0
Order By: Relevance
“…This up-regulation promotes the development of autoreactive Th17 cells. 53 Mechanisms through which dysregulated miRNAs modulate Th17/Treg balance During the development of autoimmune diseases, dysregulated miRNAs regulate Th17/Treg balance through targeting the positive or negative regulators of Th17 and/or Treg cell differentiation. 51 In addition, it has been reported that miR-663 in bone marrow-derived mesenchymal stem cells and miR-142-3p in monocyte-derived DCs suppress Treg cell development during the pathogenesis of SLE.…”
Section: T-cell Extrinsic Mirnasmentioning
confidence: 99%
See 2 more Smart Citations
“…This up-regulation promotes the development of autoreactive Th17 cells. 53 Mechanisms through which dysregulated miRNAs modulate Th17/Treg balance During the development of autoimmune diseases, dysregulated miRNAs regulate Th17/Treg balance through targeting the positive or negative regulators of Th17 and/or Treg cell differentiation. 51 In addition, it has been reported that miR-663 in bone marrow-derived mesenchymal stem cells and miR-142-3p in monocyte-derived DCs suppress Treg cell development during the pathogenesis of SLE.…”
Section: T-cell Extrinsic Mirnasmentioning
confidence: 99%
“…52 Recently, studies found that the expression of miRNA let-7i in circulating exosomes is markedly increased in patients with MS and this leads to the suppression of Treg cell development. 53 Mechanisms through which dysregulated miRNAs modulate Th17/Treg balance During the development of autoimmune diseases, dysregulated miRNAs regulate Th17/Treg balance through targeting the positive or negative regulators of Th17 and/or Treg cell differentiation. In this section, we will summarize different mechanisms through which dysregulated miRNAs modulate Th17/Treg balance during the development of autoimmune diseases (Fig.…”
Section: T-cell Extrinsic Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we found that the expression profile of miRNAs in circulating exosomes was different in patients with multiple sclerosis (MS) compared with healthy controls (HC). 1 Among them, let-7i, miR-19b, miR-25, and miR-92a were increased in exosomes from patients with MS (MS-exosome). After human primary T cells were cultured with exosomes, the frequency of regulatory T cells (Treg cell), that were determined as IFN-c À IL-17A À Foxp3 + CD4 + T cells, was lower in the presence of MS-exosome than healthy control-exosome.…”
mentioning
confidence: 99%
“…Recently, we found that the expression profile of miRNAs in circulating exosomes was different in patients with multiple sclerosis (MS) compared with healthy controls (HC) . Among them, let‐7i , miR‐19b , miR‐25 , and miR‐92a were increased in exosomes from patients with MS (MS‐exosome).…”
mentioning
confidence: 99%